A matter of presence: A qualitative study on teaching individual and collective music classes. (September 2020) - Schiavio, Andrea; Biasutti, Michele; van der Schyff, Dylan; Parncutt, Richard
In the current study, 11 expert music teachers were asked to reflect on their own practice and compare their experience of individual and collective teaching settings. Adopting an approach based on grounded theory, two interrelated themes were identified in the raw data: teaching issues and professional development . In both categories, the notion of 'presence' emerged as a defining feature of the comparison. Teachers reported to be less present in collective settings, whereas one would expect that the higher (cognitive, teaching, etc.) demands associated with more learners would result in teachers being instead more involved in the unfolding dynamics of the lesson. Inspired by the conceptual tools offered by the Extended Mind (ExM) approach, we suggest that in collective settings teachers feel less present because they can offload the cognitive role of 'teacher' onto the learners, giving rise to a hybrid extended system that fosters a shared sense of responsibility, where pedagogical dynamics are functionally distributed across the whole group. In reporting excepts from music teachers, and adopting a novel perspective to frame our discussion, our research may contribute to existing literature in (collective) music pedagogy.